PENGARUH PEMBERIAN KOMPENSASI, PENGEMBANGAN KARIR, IKATAN INTERPERSONAL, PADA KEBERTAHANAN KARYAWAN - I Dewa Made Oka Sayoga; Ni Made Ary Widiastini; Ni Kadek Sinarwati (Universitas Bina Taruna Gorontalo, 2023)
The purpose of this research is to examine the impact of compensation, opportunities for professional growth, and interpersonal relationships on the longevity of staff at Puri Raharja General Hospital. Purposive sampling was used to select 110 respondents from the Puri Raharja General Hospital employee population who met the following two criteria: received a salary lower than the federal minimum wage and had worked for more than three years. Google Forms is used for data collection in the form of surveys. Validity and reliability tests, along with normality tests and multiple linear regression, as well as partial and simultaneous t and f tests were used to analyze the data. The findings of this research prove that (1) Salary increases reduce employee incentives to stay with the company, indicating that salary compensation has a negative impact on worker retention. (2) The more progress a person makes in their career, the more likely they are to stay with the company. (3) Interpersonal relationships are important for the continuity of their work: the more they are established, the longer they stay in the company.